2021
DOI: 10.1111/andr.13001
|View full text |Cite
|
Sign up to set email alerts
|

Male seminal parameters are not associated with Leydig cell functional capacity in men

Abstract: This is an open access article under the terms of the Creative Commons Attribution-NonCommercial License, which permits use, distribution and reproduction in any medium, provided the original work is properly cited and is not used for commercial purposes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
12
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 11 publications
(17 citation statements)
references
References 60 publications
4
12
1
Order By: Relevance
“…Of the lifestyle parameters measured, and as shown earlier, 15,28,30 both higher BMI and WC appear to have a similar negative impact on INSL3, T, and cFT (Table 2). Although a different analysis, simply comparing the effect of obesity (BMI > 30) on the levels of INSL3, T, cFT, and SHBG for the phase 2 subjects also indicated a significant impact of obesity on INSL3, as well as on the other parameters (Figure S3); the impact is relatively smaller (‐9.4%) for the former than T (‐21.5%), cFT (‐14.5%), and SHBG (‐17.4%).…”
Section: Discussionsupporting
confidence: 76%
See 2 more Smart Citations
“…Of the lifestyle parameters measured, and as shown earlier, 15,28,30 both higher BMI and WC appear to have a similar negative impact on INSL3, T, and cFT (Table 2). Although a different analysis, simply comparing the effect of obesity (BMI > 30) on the levels of INSL3, T, cFT, and SHBG for the phase 2 subjects also indicated a significant impact of obesity on INSL3, as well as on the other parameters (Figure S3); the impact is relatively smaller (‐9.4%) for the former than T (‐21.5%), cFT (‐14.5%), and SHBG (‐17.4%).…”
Section: Discussionsupporting
confidence: 76%
“…Interestingly, in the multiple regression analysis (Table 3), where we have attempted to account for all possible confounding interactions between parameters in the construction of explanatory models for INSL3 and T, FSH now becomes a positive factor in determining INSL3 levels. This was also observed for the younger cohort of Swedish military conscripts 28 and suggests a role for Sertoli cells in mediating the regulation of INSL3, although not of T.…”
Section: Discussionsupporting
confidence: 56%
See 1 more Smart Citation
“… 25 However, no relationship between seminal parameters and serum INSL3 have been found so far. 26 In this study, higher INSL3 levels were found in participants with reduced sperm concentrations, but this did not reach statistical significance.…”
Section: Discussioncontrasting
confidence: 69%
“…For the male, for example, the WHO latest acceptable reference range for sperm concentration is 15-259 million per ml with progressive motility of 32-75% and for normal morphology is only > 4% (Cooper et al, 2010;WHO, 2010)! We have shown that the normal range for circulating insulin-like peptide 3 (INSL3), a measure of Leydig cell functional capacity (i.e., total number of Leydig cells in the testes compounded with their differentiation status) is 0.39-1.87 ng/mL (5%, 95% confidence intervals) in healthy young men (Anand-Ivell et al, 2021). This is a large variation, compared to other, comparable non-episodic health parameters, such as thyroxine (5.5-12.5 µg/dL) or haemoglobin (14.0-17.5 g/dL).…”
Section: The Dynamic Physiologymentioning
confidence: 99%